Long Non-coding RNAs: Regulators of Viral Infection and the Interferon Antiviral Response - Qiu, Lipeng; Wang, Tao; Tang, Qi; Li, Guohui; Wu, Peng; Chen, Keping (Frontiers in Microbiology, 2018)
Interferons (IFNs) are a family of cytokines providing a robust first line of host innate defense against pathogenic infection, and have now been part of the standard treatment for viral infection. However, IFN based therapy can best be described as modestly effective. Long non-coding RNAs (lncRNAs) are a novel class of non-protein-coding RNAs that are capable of regulating gene expression at different levels, including chromatin, transcription, post-transcription, and translation. Recently, lncRNAs are found to be deregulated upon viral infection or IFN treatment, and some of them can modulate viral infection in an IFN-dependent or -independent manner. Due to the crucial roles of lncRNAs in viral infection and the IFN antiviral response, the modulation of specific lncRNAs may be involved to increase the IFN antiviral response and improve the clinical result of IFN-based therapy. In this review, we summarize lncRNAs that are deregulated by viral infection, with special focus on the functions and underlying mechanisms of some essential lncRNAs, and discuss their roles in viral infection and the antiviral response of IFN.